(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Perineal rupture is one of the complications that occurs during labor that can lead to death in the mother. The impact of perineal rupture is bleeding during the first hour after childbirth, fistulae, hematoma, and infection. One of the preventive efforts that can be done to reduce perineal rupture is pregnancy exercises. The results of a preliminary survey conducted at PMB Dince Safrina showed that 66.1% out of 186 women giving birth experienced perineal rupture. This study aimed to determine the relationship between pregnancy exercise and perineal rupture in primiparous women in PMB Dince Safrina in 2015-2018. This quantitative research method used a cross sectional design. The population was all primiparous mothers at PMB Dince Safrina in 2015 up to 2018 with 219 people. The sampling technique used was total sampling. The data analysis used univariate and bivariate with the chi-square statistical test. The results showed that 55.25% of primiparous mothers did pregnancy exercise and 58.40% experienced perineal rupture. The results of statistical tests obtained a p-value of 0.000, meaning there was a significant relationship between pregnancy exercise and the incidence of perineal rupture in primiparous women with OR of 0.239, indicating that those who did not do pregnancy exercise would experience perineal rupture 0.239 times than those who did. It is suggested to midwives to maintain pregnancy exercise classes and provide health education to pregnant women to be more active in carrying out pregnancy exercises to prevent the occurrence of perineal rupture during labor.